2019
DOI: 10.1016/j.fsi.2018.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Growth, physiological and immune responses of Arapaima gigas (Arapaimidae) to Aeromonas hydrophila challenge and handling stress following feeding with immunostimulant supplemented diets

Abstract: The current study tested the efficacy of a dietary immunostimulant additive (Aquate Fish™ ®) on the growth performance, and on the physiological and immune responses of Arapaima gigas. Two trials were carried out: a feeding trial for 30 days with the experimental diets and a challenge trial for 7 days, in which fish were bacterial challenge (Aeromonas hydrophila) following by 60 s handling stress. During the feeding trial, fingerlings were fed diets supplemented with 0 (control), 6, 9 and 12 g Aquate Fish™ ® /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…are also considered highly pathogenic because they have been responsible for causing high mortalities on arapaima fish farms, even with low and moderate parasite loads in Brazil (Santana et al, 2017), Peru (Morey et al, 2019) and a public aquarium in Denmark (Buchmann et al, 1994). It is noteworthy that its deleterious effects are more accentuated in the initial arapaima production stages (larvae and juvenile) (Dias et al, 2019), when they undergo several morphophysiological changes and adaptations to the aquatic environment (Alcântara et al, 2019;Frommel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…are also considered highly pathogenic because they have been responsible for causing high mortalities on arapaima fish farms, even with low and moderate parasite loads in Brazil (Santana et al, 2017), Peru (Morey et al, 2019) and a public aquarium in Denmark (Buchmann et al, 1994). It is noteworthy that its deleterious effects are more accentuated in the initial arapaima production stages (larvae and juvenile) (Dias et al, 2019), when they undergo several morphophysiological changes and adaptations to the aquatic environment (Alcântara et al, 2019;Frommel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Everything indicates that in the longitudinal direction it has a smaller number of fine fibers (reticulin), and these are intended to assist in tying collagen fibers and providing resistance in progressive tearing. According to Dias et al 8 and Souza et al 13 and when fish leather has a greater amount of reticulin fibers binding the collagen fibers, this leather presents greater tear strength. Therefore, everything indicates that in the transverse and diagonal direction leather has a greater amount of reticulin fibers tying to collagen fiber bundles.…”
Section: Test 1: Physicomechanical Characteristicsmentioning
confidence: 95%
“…Everything indicates that there is a difference in the tensile strength and progressive tearing, as well as in the elasticity of the leather in relation to leather direction, tanning agents used in the tanning or retanning, although there are other factors involved, such as the amount of oil added in the process of leather grease. Dias et al 8 reported that the increase in the addition of oils in the fatliquoring stage provides a greater slip between the collagen fibers, thus shown greater flexibility or elasticity (greater stretching value). 22 According to Vieira et al 15 to 73.93% (head), in relation to leather regions.…”
Section: Test 1: Physicomechanical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the addition of proper levels of immunostimulants in the diet of aquatic animals affected the functions of nutrition, absorption and intestinal immunity positively 18–20 . Currently, the use of different types of immunostimulants including, chemical synthetic reagents, 21 bacterial derivatives, 22 fungal derivatives, 23,24 polysaccharides, 19,25–27 animal and plant extracts, 28 nutritional factor 29–32 as aquafeed additives were increased in aquatic animal feed 33 . Among them, polysaccharide immunostimulants have been widely used in aquafeed and studies revealed that they are important to promote the growth and immune function of aquatic animals.…”
Section: Introductionmentioning
confidence: 99%